Hispidulin induces mitochondrial apoptosis in acute myeloid leukemia cells by targeting extracellular matrix metalloproteinase inducer - Gao, Hui (Am J Transl Res, 2016)
Acute myeloid leukemia (AML) represents a heterogeneous group of hematological neoplasms with marked heterogeneity in response to both standard therapy and survival. Hispidulin, a flavonoid compound that is anactive ingredient in the traditional Chinese medicinal herb Salvia plebeia R. Br, has recently been reported to have anantitumor effect against solid tumors in vitro and in vivo. The aim of the present study was to investigate the effects of hispidulin on the human leukemia cell line in vitro and the underlying mechanisms of its actions on these cells. Our results showed that hispidulin inhibits AML cell proliferation in a dose- and time-dependent manner, and induces cell apoptosis throughan intrinsic mitochondrial pathway. Our results also revealed that hispidulin treatment significantly inhibits extracellular matrix metalloproteinase inducer (EMMPRIN) expression in both tested AML cell lines in a dose-dependent manner, and that the overexpression of EMMPRIN protein markedly attenuates hispidulin-induced cell apoptosis. Furthermore, our results strongly indicated that the modulating effect of hispidulin on EMMPRIN is correlated with its inhibitory effect on both the Akt and STAT3 signaling pathways.